Practical engineering drawing - Hadley, Brian (Addison Wesley Longman, 1999)
Introduces students to the basic concepts of engineering drawing and provides realistic exercises for students to practice on. The book takes the student from manual draughting through to computer-aided draughting and includes information on the use of CAD/CAM techniques.